Dear President Macron; an Ordinary People Get Anger to You (But I know you are Not Meant to Be) - Thobias Sarbunan (Syntax Corporation Indonesia, 2020)
Emanuel Macron was excavated the anger from thousands of people around the world, that society in fact was Muslim people. Therefore, number of protest escalated in many countries including Indonesia, as the biggest Muslim country in the world. I as personal, also stand in scientific circle, in fact was indeed concerned to that chaos affected by politic speech. Therefore, in short, this paper conducted to educate the widespread society, ‘who stand-out of politic activity also the system’, to bridge that society knowledge toward politic speech and related issue around politic knowledge. By the end, I see that politic knowledge was concrete and systematic, that not think before. Moreover, to react in this issue, the matter of politic speech, even the discourse that related to language-politic, how politician act through rhetorician movement, all of that knowledge must be learned and highlight to the broad people, that in purpose to prevent undesired act such violence or riot, which harmfully to all of us, even in systematic impact